2012
DOI: 10.1177/0021998312437235
|View full text |Cite
|
Sign up to set email alerts
|

The role of a silane coupling agent in carbon nanotube/polypropylene composites

Abstract: The carbon nanotube (CNT)/polypropylene(PP) composites have been prepared with the aid of a silane coupling agent (ZFDA, Dow Corning® Z‐6173) and then characterized by electron microscopic, electrical, mechanical, and thermal measurements in order to understand the role of the silane coupling agent in CNT/PP composites. It was experimentally found that the best usage of ZFDA was 20 wt% based on the CNTs. The coupling agent could effectively reduce the percolation threshold to 0.01 wt% from 2.7 wt% for electric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 37 publications
0
18
0
Order By: Relevance
“…The higher T co and T cp of the PA 6 composites compared to the unfilled PA 6 means that upon cooling, crystallization of PA 6 begins earlier in the composites than in the unfilled PA 6. This is because MCC acts as nucleating agents to induce crystallization of the polymer melt in the cooling process . Table also showed that the composite samples exhibited a lower percentage crystallinity ( X c ) than the neat polymer.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…The higher T co and T cp of the PA 6 composites compared to the unfilled PA 6 means that upon cooling, crystallization of PA 6 begins earlier in the composites than in the unfilled PA 6. This is because MCC acts as nucleating agents to induce crystallization of the polymer melt in the cooling process . Table also showed that the composite samples exhibited a lower percentage crystallinity ( X c ) than the neat polymer.…”
Section: Resultsmentioning
confidence: 97%
“…Table also showed that the composite samples exhibited a lower percentage crystallinity ( X c ) than the neat polymer. The reason why the crystallinity of PA 6 in its composites was lower than that of unfilled PA 6 can be explained that the MCC particles provide nucleating sites for crystallization of PA 6 but at the same time the mobility of PA 6 chains is restricted by the MCC particles and MCC particles may also act as barriers affecting crystal growth . The absolute crystallinity as a function of temperature is also illustrated in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Various polymers including PTFE, PI, PMMA, PS, PPS, AMMA, UHMWP, and PP have been reinforced with the CNTs [7][8][9][10][11][12][13][14][15] and extensive friction and wear performance studies have been performed. Extensive works [16][17][18][19][20][21][22][23][24] have reported the effects of the processing route and parameters on the rheological, thermal, mechanical, and electrical performances of the CNT-PP composites. This work attempts to investigate the tribological performance of the CNT-PP composites developed using the melt compounding technique.…”
Section: Introductionmentioning
confidence: 99%
“…The nucleating effect contributes significantly to the occurrence of transcrystalline layers around the nanofillers, resulting in an increase in the degree of crystallinity [27]. However, nanofillers also restrict the mobility of polymer molecular chains and act as barriers affecting crystal growth [28]. In the case of CNF as nanofillers, the latter became the predominant factor in affecting the crystallization of Nylon 6.…”
Section: Thermal Properties Of Nanocomposite Filamentsmentioning
confidence: 99%